Method for determining titanium alloy texture

The texture of titanium alloy is determined by synchronous radiation HEXRD method and combined with heat treatment parameters, the texture change trend is analyzed, and an optimized heat treatment process is formulated, which solves the problem of complex texture evolution of metastable β titanium alloy and improves the strength and plasticity of the alloy.

CN119595678AActive Publication Date: 2025-03-11NORTHWESTERN POLYTECHNICAL UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411715749.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-11
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

Metastable β-titanium alloys have complex texture evolution during heat treatment, resulting in performance anisotropy, and it is difficult for the prior art to effectively analyze and optimize their texture change trends.

Method used

The texture of titanium alloy is determined by synchronous radiation HEXRD method, combined with the parameters of solid solution and aging treatment, the changing trends of texture are analyzed, and a targeted heat treatment process is formulated to optimize the texture and performance of titanium alloy.

Benefits of technology

Accurate analysis of the texture of titanium alloy and optimization of heat treatment process are achieved, significantly improving the strength and plasticity of the alloy, and suitable for high-demand fields such as aerospace.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119595678A_ABST
    Figure CN119595678A_ABST
Patent Text Reader

Abstract

The invention relates to a method for determining a titanium alloy texture. The method comprises the following steps: preparing a sample; obtaining a Debye ring, exporting Debye ring data, and drawing a diffraction intensity-azimuth angle relation graph; the preferred orientation of the main texture is analyzed; in combination with solid solution, conversion from alpha p to beta occurs, and most equiaxed alpha phases are dissolved in a matrix phase; beta-to-alpha s transformation occurs in aging, a needle-like secondary alpha phase is separated out from a matrix phase, and the change trend of the solid solution aging texture is compared and analyzed. In addition, the invention also relates to a method for carrying out heat treatment on the titanium alloy, which is obtained according to the analysis method, and the method comprises the following steps: carrying out solution treatment; low-temperature aging treatment is conducted, specifically, the titanium alloy subjected to solution treatment is subjected to aging for 3-5 h at the temperature of 250-350 DEG C, and then air cooling is conducted to the room temperature; and high-temperature aging treatment is conducted, specifically, the titanium alloy subjected to low-temperature aging treatment is subjected to heat preservation for 5-7 h at 500-550 DEG C, and then air cooling is conducted to the room temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure generally relates to the research and development of titanium alloys, and more particularly to the analysis of the microstructure evolution of titanium alloys for the research and development of new titanium alloys, and more particularly to a research method for measuring the texture of titanium alloys to analyze the microstructure evolution of titanium alloys during heat treatment. In addition, the present invention also relates to a titanium alloy heat treatment process formulated by the method for measuring the texture of titanium alloys. Background Art

[0002] Titanium alloys have the advantages of high specific strength, good corrosion resistance, excellent high and low temperature resistance, and good biocompatibility. They are widely used in aerospace, medical equipment, consumer electronics, chemical metallurgy and other fields.

[0003] The main phase composition of titanium alloy can be divided into three categories: α phase, β phase and α+β phase. Among them, metastable β titanium alloy has a high heat treatment strengthening effect, and solid solution aging treatment can significantly improve the strength and plasticity of the alloy, so it has broad application prospects in high-demand fields such as aerospace.

[0004] The two-phase structure of metastable β titanium alloy is mainly composed of β phase and α phase. The β phase usually has a body-centered cubic (bcc) crystal structure, while the α phase has a hexagonal close-packed (hcp) crystal structure. The microstructure of metastable β titanium alloy usually includes α phase precipitates and a stable β matrix. The production is often achieved by solid solution aging strengthening process to generate fine dispersed secondary nano-α phase (α s Phase) to strengthen the alloy. However, due to the processing history of forging and drawing, the metastable β titanium alloy inevitably has uneven orientation inside, and the resulting texture constitutes anisotropy in the alloy properties. During the solution aging process, these textures have a complex development trend with the changes in heat treatment parameters and the phase composition of the alloy, which limits the application of the alloy.

[0005] The processing history of metastable β titanium alloy materials causes the preferred orientation inside the alloy. During the solid solution aging strengthening process, the texture of these preferred orientations will undergo complex evolution. Therefore, studying different texture evolution mechanisms, reasonably explaining the texture type and evolution process, and clarifying the texture type and strength change results of metastable β titanium alloy in α phase and β phase during solid solution aging have become important ways to study and develop metastable β titanium alloys. For example, Zhang Junsong et al. studied Ti 3 Two different texture evolution mechanisms of Sn / TiNi eutectic soft-hard dual-phase composites during compression provide a reasonable explanation for the texture type and evolution process.

[0006] The synchrotron radiation HEXRD method has become a powerful tool for studying metals and alloys with its high angular resolution and strong penetration ability. The Debye rings obtained contain not only the diffraction angle and the diffraction peak information of the corresponding crystal plane, but also the diffraction intensity information of a certain diffraction ring at the macroscopic azimuth of the sample. When the intensity fluctuation is observed, the existence of texture can be easily judged. By extracting the data of the corresponding ring, a one-dimensional diffraction intensity curve that changes with the azimuth angle of 0° to 360° can be drawn. The texture is divided according to the relationship between these curves and the extrusion direction (AD) and the cylindrical radial direction (RD). For multi-organization structures or textures before and after turning, the microscopic crystal coordinate system and the macroscopic sample coordinate system are linked, and the information of one-organization structure is corresponded to the two coordinate systems to deduce the orientation of other textures relative to it.

[0007] In addition, treating titanium alloys through heat treatment such as solution treatment and aging treatment is an important method to eliminate the internal stress of titanium alloys after machining such as extrusion and improve their comprehensive properties. The titanium alloy heat treatment process is formulated by the method of determining the titanium alloy texture.

[0008] The appearance of texture will affect the uniformity and isotropy of the titanium alloy's organization, and thus negatively affect its mechanical properties. Therefore, the inventors of the present invention have considered how to apply the synchrotron radiation HEXRD method to analyze the texture of titanium alloys in the existing development technology of titanium alloys, so as to develop new titanium alloys or improve titanium alloy processing technology, especially heat treatment technology, in view of the fact that the existing technology has not yet obtained a titanium alloy with target performance by analyzing the influence of the heat treatment process on the trend of texture changes. The inventors of the present invention have further thought of how to analyze the heat treatment process of how to obtain the target titanium alloy texture by analyzing the influence of the heat treatment process on the titanium alloy texture, thereby formulating a titanium alloy heat treatment process to obtain the target performance. Summary of the invention

[0009] The inventors of the present invention believe that solution aging treatment significantly enhances α s The texture strength of the phase makes the α s Phase variants precipitate preferentially, so it is proposed that for a two-phase structure, namely the equiaxed α phase (α pPhase) and β matrix phase, after solution treatment in the two-phase region, different parameters of aging treatment were carried out in groups. The evolution of the internal texture of the alloy has its own characteristics. Using synchrotron radiation technology, and by combining the analysis of the micro-orientation of the grains and the macroscopic azimuth of the sample, the texture between different phases can be distinguished, and the texture type and strength information generated during the solution aging process and the transformation before and after heat treatment can be determined. Therefore, the processing method for metastable β titanium alloy is improved, and the strength and plasticity of the alloy are significantly improved by using the high heat treatment strengthening effect and solution aging treatment. This has broad application prospects in high-demand fields such as aerospace.

[0010] According to a specific embodiment of the present invention, a method for measuring the texture of a titanium alloy is provided, comprising the following steps:

[0011] Step 1: Prepare the sample

[0012] From the forged extruded titanium alloy forging, cylindrical specimens are cut from the center by a CNC wire cutting machine, and then divided into several groups, such as but not limited to three groups, four groups, five groups, etc.

[0013] The cylindrical samples are first subjected to solution treatment, and then the first group of samples are subjected to high temperature aging treatment, the second group of samples are subjected to low temperature aging treatment, and the third group of samples are subjected to low temperature aging and high temperature aging in sequence. After aging, each group of cylindrical samples is air-cooled to room temperature. The three groups of cylindrical samples are cited only as examples and do not constitute any limitation to the present invention.

[0014] Step 2: Obtain the Debye ring and export the Debye ring data

[0015] The samples were treated differently and cooled to room temperature. Synchrotron radiation high energy X-ray diffraction (HEXRD) experiments were carried out to extract the diffraction intensity of the Debye rings of the samples, which varied significantly with the azimuth angle, such as β(110), β(200), α(0002), The diffraction ring data is plotted as a diffraction intensity-azimuth angle relationship diagram;

[0016] Step 3: Analyze the preferred orientation of the main texture

[0017] Analyze the preferred orientation of the main texture according to the angle and intensity information in the diffraction intensity-azimuth;

[0018] Step 4: Analyze and obtain the texture change trend

[0019] Combined solid solution occurs p →β transformation, most of the equiaxed α phase is dissolved in the matrix phase; β→α s The needle-shaped secondary α phase precipitates from the matrix phase during the solid solution aging process, and the changing trend of the solid solution aging texture is compared and analyzed.

[0020] Preferably, the titanium alloy is a solid solution metastable β titanium alloy. Further preferably, the metastable β titanium alloy contains 3-5 at.% Al, 5-7 at.% V, 4-6 at.% Al, 2-4 at.% Cr, 3-5 at.% Al, 0-2 at.% Zr, and the remainder is Ti and unavoidable impurities. Further preferably, the titanium alloy is Ti-4Al-6V-5Mo-3Cr-1Zr.

[0021] Preferably, the solution treatment is to treat the alloy at 780-800°C for 0.5-1h and then air-cool it to room temperature, the low-temperature aging treatment is to age the titanium alloy at 250-350°C for 3-5h and then air-cool it to room temperature, and the high-temperature aging treatment is to keep the titanium alloy at 500-550°C for 5-7h and then air-cool it to room temperature.

[0022] Further preferably, in the solution treatment, the titanium alloy is solution treated at 795°C for 0.5 h and then air-cooled to room temperature; in the low-temperature aging, the titanium alloy is aged at 300°C for 4 h and then air-cooled to room temperature; in the high-temperature aging, the titanium alloy is kept at 520°C for 6 h and then air-cooled to room temperature.

[0023] According to a specific embodiment of the present invention, a method for formulating a heat treatment process for a titanium alloy is provided by using the method for determining the texture of the titanium alloy as described above.

[0024] First, the samples were subjected to different heat treatment processes, their textures were analyzed, and the heat treatment process corresponding to the sample with the highest proportion of target texture was found. Then, the corresponding heat treatment process was determined and improved, which specifically included the following steps:

[0025] Step 1: Prepare the sample

[0026] From the forged extruded titanium alloy forging, cylindrical specimens are cut from the center by a CNC wire cutting machine and divided into several groups, such as but not limited to three, four, and five groups of specimens.

[0027] Take three groups of samples as an example for explanation. First, each group of samples is subjected to solution treatment. Then, the first group of samples is subjected to high-temperature aging treatment, that is, it is subjected to solution treatment + high-temperature aging treatment; the second group of samples is subjected to low-temperature aging treatment, that is, it is subjected to solution treatment + low-temperature aging treatment; the third group of samples is subjected to low-temperature aging and high-temperature aging in sequence, that is, it is subjected to solution treatment + low-temperature aging + high-temperature aging treatment. After the above aging, the three groups of cylindrical samples are air-cooled to room temperature;

[0028] Step 2: Obtain the Debye ring and export the Debye ring data

[0029] The room temperature samples obtained in different states were subjected to synchrotron radiation high energy X-ray diffraction (HEXRD) experiments to extract the diffraction intensity of the Debye rings of the samples, which varied significantly with the azimuth angle, such as β(110), β(200), α(0002), The diffraction ring data is plotted as a diffraction intensity-azimuth angle relationship diagram;

[0030] Step 3: Analyze the preferred orientation of the main texture

[0031] Analyze the preferred orientation of the main texture according to the angle and intensity information in the diffraction intensity-azimuth;

[0032] Step 4: Analyze and obtain the texture change trend

[0033] Combined solid solution occurs p →β transformation, most of the equiaxed α phase is dissolved in the matrix phase; β→α s The needle-shaped secondary α phase precipitates from the matrix phase during the solid solution aging process, and the changing trend of the solid solution aging texture is compared and analyzed.

[0034] Step 5: Develop heat treatment process

[0035] The types and strengths of the textures in the multiple groups of cylindrical specimens are compared to find the group with the least texture, and a heat treatment process for obtaining a titanium alloy with uniform and isotropic structure is developed and improved according to the heat treatment process it has undergone.

[0036] Preferably, the solution treatment is to subject the alloy to solution treatment at 780-800° C. for 0.5-1 h and then air-cool to room temperature.

[0037] Preferably, the low temperature aging treatment is to age the titanium alloy at 250-350° C. for 3-5 hours, and then air cool to room temperature.

[0038] Preferably, the high temperature aging treatment is to keep the titanium alloy at 500-550° C. for 5-7 hours and then air-cool it to room temperature.

[0039] Further preferably, in the solution treatment, the titanium alloy is solution treated at 795°C for 0.5 h and then air-cooled to room temperature; in the low-temperature aging, the titanium alloy is aged at 300°C for 4 h and then air-cooled to room temperature; in the high-temperature aging, the titanium alloy is kept at 520°C for 6 h and then air-cooled to room temperature.

[0040] More preferably, the titanium alloy is a metastable β titanium alloy, containing 3-5 at.% Al, 5-7 at.% V, 4-6 at.% Al, 2-4 at.% Cr, 3-5 at.% Al, 0-2 at.% Zr, and the balance is Ti and unavoidable impurities. More preferably, the titanium alloy is Ti-4Al-6V-5Mo-3Cr-1Zr.

[0041] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0042] 1. Traditional texture analysis is mainly carried out through the information in the pole figures and anti-pole figures output by EBSD test, which can usually only obtain the crystal structure and orientation information of the local area, and cannot fully reflect the texture characteristics of the entire sample. The selection of technical parameters such as step size and image calibration will affect the accuracy of grain or unit size calculation. In this method, the hard X-rays generated by synchrotron radiation have high energy and deep penetration capabilities, and can quickly obtain diffraction information of the entire volume without destroying the sample.

[0043] 2. Compared with traditional analysis methods, this method can accurately express the macroscopic preferred orientation of the entire sample and accurately reflect the complex orientation relationship inside the crystal.

[0044] 3. The present invention compares the types and strengths of textures in the multiple groups of cylindrical specimens to find the group with the least texture, and formulates and improves the heat treatment process for obtaining a titanium alloy with uniform and isotropic structure based on the heat treatment process it has undergone. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] The above and other purposes, features and advantages of the present disclosure will become more apparent by describing the embodiments of the present disclosure in more detail in conjunction with the accompanying drawings. The accompanying drawings are used to provide a further understanding of the embodiments of the present disclosure and constitute a part of the specification. Together with the embodiments of the present disclosure, they are used to explain the present disclosure and do not constitute a limitation of the present disclosure. In the drawings, the same reference numerals generally represent the same components or steps.

[0046] Figure 1 A diffraction intensity-azimuth angle relationship diagram obtained according to Example 1 of the present disclosure is shown;

[0047] Figure 2 In a) and b) Figure 1 The cell orientation of the β-phase and α-phase corresponding to the strongest set of preferred orientations in the graph, c) and d) show the relative positions of the preferred orientations of the main textures of the two phases in the sphere after the cell of the β-phase and α-phase are placed at the center of the Ewald sphere;

[0048] Figure 3 In a), it is shown that by Figure 2a) shows the preferred orientation position of the secondary texture after the β-phase unit cell is rotated 30° clockwise around the X-axis of the sphere, b) and c) show the preferred orientation position of the secondary texture after the β-phase unit cell is rotated 30° clockwise around the X-axis of the sphere, and Figure 2 b) The preferred orientation position of the secondary texture after the α-phase unit cell is rotated 15° counterclockwise and 45° clockwise around the X-axis of the sphere;

[0049] Figure 4 A diffraction intensity-azimuth angle relationship diagram of Example 2 of the present disclosure is shown;

[0050] Figure 5 A diffraction intensity-azimuth angle relationship diagram of Example 3 of the present disclosure is shown;

[0051] Figure 6 The preferred orientation diagram of the texture of Example 3 of the present disclosure is shown, wherein a) and b) show the preferred orientation diagram of the α phase texture in the solid solution state, and c) and d) show the preferred orientation diagram of the α phase texture in the solid solution state. Figure 6 The preferred orientation position of the texture in the solid solution + high temperature aging state is obtained by rotating the α-phase unit cell in a) and b) 35° clockwise around the X-axis of the Ewald sphere;

[0052] Figure 7 A diffraction intensity-azimuth angle relationship diagram obtained according to Example 4 of the present disclosure is shown;

[0053] Figure 8 A diffraction intensity-azimuth angle relationship diagram obtained according to Example 4 of the present disclosure is shown. DETAILED DESCRIPTION

[0054] Below, the exemplary embodiments according to the present disclosure will be described in detail with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present disclosure, rather than all the embodiments of the present disclosure, and it should be understood that the present disclosure is not limited to the exemplary embodiments described here.

[0055] The inventors of the present invention propose a texture research method using the above-mentioned synchrotron radiation HEXRD method, which is carried out in the following steps:

[0056] (1) Titanium alloys were prepared and subjected to synchrotron radiation HEXRD detection after several different heat treatments. The cylindrical specimens used in the experiment were placed horizontally with the axial direction (AD) as the extrusion direction and perpendicular to the incident beam. The two radial directions (RD) were perpendicular and parallel to the incident beam, respectively. The azimuth angles in the Debye ring corresponding to the axial and radial directions perpendicular to the incident beam were 0° and 90°, respectively. The synchrotron radiation data obtained were processed using software such as Fit2D and Origin. The relative positions of the multi-organization structures in the gold, the orientation changes of the main textures in each phase under different heat treatment conditions, and the changes in the strength of the textures before and after heat treatment were quantitatively described by combining the changes in the intensity and azimuth of the preferred orientation in the image with the information of the two-phase crystal structure.

[0057] (2) After obtaining the Debye rings of the sample, select the diffraction rings whose diffraction intensity varies significantly at different azimuth angles, that is, the diffraction rings with preferred orientation, and derive the one-dimensional diffraction data of the selected diffraction rings varying at different azimuth angles.

[0058] (3) Compare the preferred orientation angles and strength information under different states, summarize the texture types within a single sample and the changes in texture between different samples, and give a reasonable explanation based on the microstructure and phase change.

[0059] (4) Based on the preferred orientation information of a certain structure, a unit cell that meets the conditions is drawn and placed at the center of the Ewald sphere. By rotating the unit cell around the sphere, the texture position that meets other preferred orientations is obtained.

[0060] Example

[0061] The present invention is further described below in conjunction with examples of characterization of material texture, but the present invention is not limited to the following examples.

[0062] Example 1

[0063] This example is aimed at the texture analysis of the metastable β titanium alloy Ti-4Al-6V-5Mo-3Cr-1Zr (the numbers represent the atomic percentage in the alloy, the same below, the remainder is Ti and unavoidable impurities). The analysis is achieved by the following steps:

[0064] (1) Sample preparation

[0065] The titanium alloy ingot is first forged at 850-950°C, air-cooled to room temperature after unloading, extruded above the β phase transformation temperature, and then cut into pieces of size The cylindrical specimen was ground and polished.

[0066] (2) Export Debye ring data

[0067] The sample was subjected to synchrotron radiation HEXRD detection. The axial direction (AD) of the cylindrical sample was the extrusion direction and it was placed horizontally perpendicular to the incident light beam. The two radial directions (RD) were perpendicular and parallel to the incident light beam, respectively. The azimuth angles in the Debye ring corresponding to the axial direction and the radial direction perpendicular to the incident light beam were 0° and 90°, respectively. The obtained synchrotron radiation data were processed using software such as Fit2D and Origin, thereby obtaining the Debye ring of the sample.

[0068] In Fit2D software, the radius range of the target diffraction ring is selected by using the tools "INNER RADIUS" and "OUTER RADIUS", and the data within the selected ring is integrated through the "INTEGRATE" operation to extract the diffraction intensity of the sample Debye ring that changes significantly with the azimuth angle, β(110), β(200), α(0002), Diffraction ring data and plotted as Figure 1 .

[0069] (3) Preferred orientation of main texture

[0070] according to Figure 1 The diffraction intensity-azimuth angle relationship diagram in the figure distinguishes and summarizes the preferred orientation of the main textures.

[0071] (4) Draw the Ewald sphere

[0072] According to the preferred orientation information of the main filament texture of β phase and α phase, the unit cell that meets the conditions is drawn as follows Figure 2 As shown in a) and b), after placing the unit cell at the center of the Ewald sphere, the relative positions of the preferred orientations of the two phases in the sphere are as follows Figure 2 As shown in c) and d).

[0073] (5) β phase texture relationship

[0074] exist Figure 1 In addition to the β phase Figure 2 The silk texture shown in c) also has some relatively weak silk textures at other angles. Figure 2 c) The β-phase unit cell is rotated 30° clockwise around the X-axis of the sphere to obtain Figure 3 a), we can see that the texture orientation after rotation is Figure 1 The orientation of the weaker texture of the β phase is basically consistent.

[0075] (6) α phase texture relationship

[0076] exist Figure 1 In addition to the α phase Figure 2 d) shows the silk texture, and there are some relatively weak silk textures at other angles. For the secondary texture in the α phase, such as Figure 3 As shown in b) and c), by Figure 2 d) After the α-phase unit cell is rotated 15° counterclockwise and 45° clockwise around the X-axis of the sphere, the new preferred orientation direction is Figure 1 The orientation of the weaker texture of the α phase is basically consistent.

[0077] from Figure 1 as well as Figure 2a) and c) show that the main filament texture in the β phase is the β phase with an angle of 45° with the AD and RD of the cylindrical sample. <110> and β near the AD and RD directions <200> .from Figure 1 as well as Figure 2 b) and d) show that the main silk texture in the α phase is the α phase with an angle of 45° to AD and RD. <0002> and By rotating the Ewald ball, Figure 3 a) It can be seen that the angle between the two structures in the alloy β phase is 30°. Figure 3 b) and c) show that the relationship between the ternary structure in the α phase and the axial AD is 0°, 45°, and 60° respectively.

[0078] Example 2

[0079] This embodiment is for the solid solution metastable β titanium alloy Ti-4Al-6V-5Mo-3Cr-1Zr texture analysis, the analysis results are achieved by the following steps:

[0080] (1) Sample preparation

[0081] The titanium alloy was first subjected to forging and extrusion as in Example 1, then subjected to solution treatment at 795°C for 0.5 h, air-cooled to room temperature, and cut into pieces of size of the specimens and grind and polish them.

[0082] (2) Export Debye ring data:

[0083] The sample was subjected to synchrotron radiation HEXRD detection. The axial direction (AD) of the cylindrical sample was the extrusion direction and it was placed horizontally perpendicular to the incident light beam. The two radial directions (RD) were perpendicular and parallel to the incident light beam, respectively. The azimuth angles in the Debye ring corresponding to the axial direction and the radial direction perpendicular to the incident light beam were 0° and 90°, respectively. The obtained synchrotron radiation data were processed using software such as Fit2D and Origin, thereby obtaining the Debye ring of the sample.

[0084] In Fit2D software, the radius range of the target diffraction ring is selected by using the tools "INNER RADIUS" and "OUTER RADIUS", and the data within the selected ring is integrated through the "INTEGRATE" operation to extract the diffraction intensity of the sample Debye ring that changes significantly with the azimuth angle, β(110), β(200), α(0002), The diffraction ring data is plotted as Figure 4 The diffraction intensity-azimuth angle relationship diagram is shown.

[0085] (3) Main texture preferred orientation:

[0086] according to Figure 4 The angle and intensity information in the image are used to analyze the preferred orientation of the main texture.

[0087] (4) Analysis of the texture change trend of β phase and α phase:

[0088] Combined solid solution occurs p →β transformation, most of the equiaxed α phase is dissolved in the matrix phase, and the orientation and strength change trends of the alloy texture before and after solution treatment are compared and analyzed.

[0089] Depend on Figure 4 It can be seen that the texture orientation information before and after the solid solution remains basically unchanged, and the texture strength of the alloy generally shows a trend of increasing the β phase and decreasing the α phase. The main filament texture in the β phase is the β phase with an angle of 45° with the AD and RD of the cylindrical specimen. <110> and β near the AD and RD directions <200> The main silk texture in the α phase is α with an angle of 45° with AD and RD. <0002> and The main texture strengths of β(110) and β(200) increased to 161.7% and 155.8% of the original, respectively.

[0090] Example 3

[0091] This example performs texture analysis on the metastable β titanium alloy Ti-4Al-6V-5Mo-3Cr-1Zr, and the analysis results are obtained by the following steps:

[0092] (1) Sample preparation

[0093] Solution aging treatment: The titanium alloy was first subjected to forging and extrusion as in Example 1. The alloy was subjected to solution treatment at 795°C for 0.5 h, then air-cooled to room temperature, and then subjected to high-temperature aging at 520°C for 6 h, and then air-cooled to room temperature. The titanium alloy subjected to solution treatment and high-temperature aging treatment was cut into pieces of size The specimens were ground and polished.

[0094] (2) Export Debye ring data:

[0095] The sample was subjected to synchrotron radiation HEXRD detection. The axial direction (AD) of the cylindrical sample was the extrusion direction and it was placed horizontally perpendicular to the incident light beam. The two radial directions (RD) were perpendicular and parallel to the incident light beam, respectively. The azimuth angles in the Debye ring corresponding to the axial direction and the radial direction perpendicular to the incident light beam were 0° and 90°, respectively. The obtained synchrotron radiation data were processed using software such as Fit2D and Origin, thereby obtaining the Debye ring of the sample.

[0096] In Fit2D software, the radius range of the target diffraction ring is selected by using the tools "INNER RADIUS" and "OUTER RADIUS", and the data within the selected ring is integrated through the "INTEGRATE" operation to extract the diffraction intensity of the sample Debye ring that changes significantly with the azimuth angle, β(110), β(200), α(0002), The diffraction ring data is plotted as Figure 5 The diffraction intensity-azimuth angle relationship diagram is shown.

[0097] (3) Draw the Ewald sphere

[0098] observe Figure 5 The preferred orientation angle of the α phase in the solid solution state was found to be different from that of the α phase in Example 2. The silk texture of the α phase after high temperature aging was reversed. In order to explore the relationship between the preferred orientation of the α phase before and after high temperature aging, the Ewald sphere of the α phase solid solution texture was drawn with reference to the conclusion in Example 2. Figure 6 a) and b) are textures with an angle of 45° and 60° to AD, respectively, and they are obtained by rotating them. Figure 6 c), d), and Figure 5 The preferred orientation angle of the α phase in the sample is basically consistent.

[0099] (4) Analysis of the texture change trend of β phase and α phase combined with high temperature aging to produce β→α s Transformation precipitation α s Phase. Figure 5 The angle and strength information in the alloy are used to compare and analyze the orientation and strength change trends of the alloy texture before and after high-temperature aging treatment. Figure 5 It can be seen that compared with the solid solution state, the texture strength of β(110) and β(200) is reduced by more than 80%, mainly distributed in the AD direction. The orientation is closer to the AD and RD directions, and the texture strength is enhanced by 119.2% and 584.2% respectively. Figure 6 As shown in a) and b), the unit cell is rotated 35° clockwise around the X-axis of the Ewald sphere, as shown in Figure 6 As shown in c) and d), it can be seen that the texture turns to the direction with an angle of about 80° and 25° with AD, respectively, which indicates that α s The texture of the phase is relatively p The angle between them is about 30°.

[0100] Example 4

[0101] In this embodiment, the texture analysis of the metastable β titanium alloy Ti-4Al-6V-5Mo-3Cr-1Zr is carried out, and the analysis results are specifically achieved by the following steps:

[0102] (1) Preparation of samples:

[0103] The titanium alloy is first subjected to forging and extrusion as in Example 1, and then subjected to solution treatment. The alloy is solution treated at 795°C for 0.5 h and then air-cooled to room temperature. Then, the titanium alloy is subjected to low-temperature aging treatment, and is kept at 300°C for 4 h. After low-temperature aging treatment, the titanium alloy is air-cooled to room temperature, and the titanium alloy cooled to room temperature is cut into pieces of size The sample is ground and polished. (2) Export Debye ring data:

[0104] The sample was tested by synchrotron radiation HEXRD. The axial direction (AD) of the cylindrical sample was the extrusion direction, and it was placed horizontally perpendicular to the incident beam. The two radial directions (RD) were perpendicular and parallel to the incident beam, respectively. The azimuth angles of the axial direction and the radial direction perpendicular to the incident beam in the Debye ring were 0° and 90°, respectively. The obtained synchrotron radiation data were processed using software such as Fit2D and Origin, thereby obtaining the Debye ring of the sample.

[0105] In Fit2D software, the radius range of the target diffraction ring is selected by using the tools "INNER RADIUS" and "OUTER RADIUS", and the data in the selected ring is integrated through the "INTEGRATE" operation to obtain the sample Debye ring, and the diffraction intensity of the sample Debye ring that changes significantly with the azimuth angle is extracted, such as β(110), β(200), α(0002), The diffraction ring data is plotted as Figure 7 The diffraction intensity-azimuth angle relationship diagram is shown.

[0106] (3) Analysis of the texture change trend of β phase and α phase

[0107] according to Figure 7 The angle and strength information in the alloy are used to compare the orientation and strength change trends of the alloy texture before and after low temperature aging. Figure 7 The preferred orientation of the β phase and α phase is greatly enhanced. Figure 7 It can be seen from the comparison that the texture orientation information before and after low temperature aging remains basically unchanged. The main silk texture in the β phase is the β phase with an angle of 45° with the AD and RD of the cylindrical sample. <110> and β near the AD and RD directions <200> The main silk texture in the α phase is α with an angle of 45° with AD and RD. <0002> and Compared with the solid solution state, β(110) is enhanced by 518.5% in the direction of 45° with AD and RD; β(200) is enhanced by 298.1% in the direction near RD. The enhancement is 325.2% in the direction of 45° to AD and RD.

[0108] Example 5

[0109] In this embodiment, the metastable β titanium alloy Ti-4Al-6V-5Mo-3Cr-1Zr is subjected to texture analysis. The titanium alloy is subjected to solid solution + double-stage aging (low temperature aging followed by high temperature aging) treatment. The specific operation steps are as follows:

[0110] (1) Preparation of samples:

[0111] The titanium alloy is first subjected to forging and extrusion as in Example 1, and the titanium alloy is subjected to solution treatment, the alloy is solution treated at 795°C for 0.5h and then air-cooled to room temperature; then it is subjected to low-temperature aging treatment, the titanium alloy after solution treatment is aged at 300°C for 4h, and then air-cooled to room temperature; then the titanium alloy is subjected to high-temperature aging treatment, the titanium alloy subjected to low-temperature aging treatment is kept at 520°C for 6h, and then air-cooled to room temperature; the titanium alloy subjected to solution + double-stage aging treatment is cut into pieces of size of the specimens and grind and polish them.

[0112] (2) Export Debye ring data:

[0113] The sample was tested by synchrotron radiation HEXRD. The axial direction (AD) of the cylindrical sample was the extrusion direction, and it was placed horizontally perpendicular to the incident beam. The two radial directions (RD) were perpendicular and parallel to the incident beam, respectively. The azimuth angles of the axial direction and the radial direction perpendicular to the incident beam in the Debye ring were 0° and 90°, respectively. The obtained synchrotron radiation data were processed using software such as Fit2D and Origin, thereby obtaining the Debye ring of the sample.

[0114] In Fit2D software, the radius range of the target diffraction ring is selected by using the tools "INNER RADIUS" and "OUTER RADIUS", and the data in the selected ring is integrated through the "INTEGRATE" operation to obtain the sample Debye ring, and the diffraction intensity of the sample Debye ring that changes significantly with the azimuth angle is extracted, such as β(110), β(200), α(0002), The diffraction ring data is plotted as Figure 8 The diffraction intensity-azimuth angle relationship diagram is shown.

[0115] (3) Analysis of the texture change trend of β phase and α phase

[0116] according to Figure 8 The angle and strength information in the image are used to compare the orientation and strength change trends of the alloy texture before and after double-stage aging.

[0117] like Figure 8 As shown, compared Figure 4In the solid solution state, in the AD and RD directions, the texture strength of β(110) and β(200) decreased by 82.8% and 12.8%, respectively, mainly distributed in the AD direction; α(0002), The texture strength of the α phase and the β phase increased by 64.0% and 302.3% respectively. Combined with the results of solution treatment and high temperature aging in Example 3, the texture strength and preferred orientation position of the α phase and the β phase after the double-stage aging treatment are similar to the experimental results after high temperature aging.

[0118] By comparing the above embodiments, it can be seen that by comparing the types and strengths of textures contained in samples under different states, the group with the least texture and the weakest strength can be found. According to the heat treatment process it undergoes, a good foundation is laid for formulating and improving the heat treatment process for obtaining titanium alloys with uniform and isotropic structure.

[0119] For example, in order to obtain a titanium alloy with lower texture strength of β phase β(110) and β(200) in AD and RD directions compared with the solid solution state, a solution treatment + high temperature aging heat treatment process can be designed, or even more preferably, as in the present invention, the metastable β titanium alloy Ti-4Al-6V-5Mo-3Cr-1Zr is first subjected to forging and extrusion, and then subjected to solution treatment, the alloy is solution treated at 795°C for 0.5h and then air-cooled to room temperature; then the titanium alloy is subjected to high temperature aging treatment, kept at 520°C for 6h; and then air-cooled to room temperature, and the final β phase texture strength is reduced by more than 80%.

[0120] For another example, if a heat treatment process for a titanium alloy is desired in which the texture strength mainly distributed in the AD directions β(110) and β(200) is significantly reduced, a heat treatment process can be adopted in which the metastable β titanium alloy Ti-4Al-6V-5Mo-3Cr-1Zr is first subjected to solid solution treatment, and then subjected to low temperature aging and high temperature aging in sequence, and then air-cooled to room temperature.

[0121] In summary, embodiments 1-5, the present invention has the following characteristics:

[0122] 1. The data for the titanium alloy texture study was obtained from the synchrotron radiation HEXRD experiment.

[0123] 2. Draw the azimuth angle-diffraction intensity curve of the diffraction ring and analyze the orientation and intensity changes of the corresponding α-phase and β-phase textures.

[0124] 3. Draw the unit cell according to the preferred orientation angle of the main texture, combine the crystal coordinate system with the sample coordinate system, and drive the orientation change of the unit cell at the center of the sphere through the rotation of the Ewald sphere, and make it consistent with the orientation of the secondary texture, so as to reflect the relative position of multiple textures in a single phase and the orientation of the texture before and after heat treatment.

[0125] The basic principles of the present disclosure are described above in conjunction with specific embodiments. However, it should be noted that the advantages, strengths, effects, etc. mentioned in the present disclosure are only examples and not limitations, and it cannot be considered that these advantages, strengths, effects, etc. are required by each embodiment of the present disclosure. In addition, the specific details disclosed above are only for the purpose of illustration and ease of understanding, and are not limitations. The above details do not limit the present disclosure to the necessity of adopting the above specific details to be implemented.

[0126] The block diagrams of the devices, apparatuses, equipment, and systems involved in this disclosure are only illustrative examples and are not intended to require or imply that they must be connected, arranged, and configured in the manner shown in the block diagrams. As will be appreciated by those skilled in the art, these devices, apparatuses, equipment, and systems can be connected, arranged, and configured in any manner. Words such as "including," "comprising," "having," and the like are open words, referring to "including but not limited to," and can be used interchangeably therewith. The words "or" and "and" used herein refer to the words "and / or," and can be used interchangeably therewith, unless the context clearly indicates otherwise. The word "such as" used herein refers to the phrase "such as but not limited to," and can be used interchangeably therewith.

[0127] It should also be noted that in the apparatus, device and method of the present disclosure, each component or each step can be decomposed and / or recombined. Such decomposition and / or recombination should be regarded as equivalent solutions of the present disclosure.

[0128] The above description of the disclosed aspects is provided to enable any person skilled in the art to make or use the present disclosure. Various modifications to these aspects will be readily apparent to those skilled in the art, and the general principles defined herein may be applied to other aspects without departing from the scope of the present disclosure. Therefore, the present disclosure is not intended to be limited to the aspects shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

[0129] The above description has been given for the purpose of illustration and description. In addition, this description is not intended to limit the embodiments of the present disclosure to the forms disclosed herein. Although multiple example aspects and embodiments have been discussed above, those skilled in the art will recognize certain variations, modifications, changes, additions and sub-combinations thereof.

Claims

1. A method for measuring titanium alloy texture, comprising the following steps: Step 1: Prepare the sample Cutting cylindrical specimens from the center of a forged extruded titanium alloy forging, dividing the cylindrical specimens into a plurality of groups and subjecting them to different subsequent treatments to obtain room temperature specimens for obtaining Debye rings; Step 2: Obtain the Debye ring and export the Debye ring data A synchrotron radiation high energy X-ray diffraction (HEXRD) experiment is performed on the cylindrical sample at room temperature after different subsequent treatments, and the β(110), β(200), α(0002), and α(10_1_1) diffraction ring data of which the diffraction intensity in the sample Debye ring changes significantly with the azimuth angle are extracted and plotted into a diffraction intensity-azimuth angle relationship diagram; Step 3: Analyze the preferred orientation of the main texture Analyze the preferred orientation of the main texture according to the angle and intensity information in the diffraction intensity-azimuth; Step 4: Analyze and obtain the texture change trend Combined solid solution occurs p →β transformation, most of the equiaxed α phase is dissolved in the matrix phase; β→α s Transformation, needle-shaped secondary α phase precipitates from the matrix phase, and compared with the titanium alloy simply subjected to solid solution, an effective texture change trend is obtained.

2. The method according to claim 1, wherein: The titanium alloy is a metastable β titanium alloy in a solid solution state. The cylindrical specimens are divided into three groups, which are subjected to solution treatment + high temperature aging treatment, solution treatment + low temperature aging treatment, and solution treatment + low temperature aging + high temperature aging treatment, respectively. After aging, they are air-cooled to room temperature.

3. The method according to claim 1 or 2, wherein: The titanium alloy is a metastable β titanium alloy, containing 3-5 at.% Al, 5-7 at.% V, 4-6 at.% Al, 2-4 at.% Cr, 3-5 at.% Al, 0-2 at.% Zr, and the remainder is Ti and unavoidable impurities.

4. The method according to claim 3, wherein: The titanium alloy is Ti-4Al-6V-5Mo-3Cr-1Zr.

5. The method according to claim 2, wherein: The solution treatment is to perform a solution treatment on the titanium alloy at 795° C. for 0.5 h and then air cool it to room temperature; The low temperature aging treatment is to age the solution treated titanium alloy at 250-350°C for 3-5h, and then air cool it to room temperature; The high temperature aging treatment is to keep the titanium alloy subjected to the low temperature aging treatment at 500-550° C. for 5-7 hours, and then air cool it to room temperature.

6. A method for formulating a titanium alloy heat treatment process by using the method for determining the titanium alloy texture according to any one of claims 1 to 5, It is characterized in that The steps include: Step 1: Prepare the sample Cutting identical cylindrical specimens from the center of a forged extruded titanium alloy forging by a numerically controlled wire cutting machine, dividing the cylindrical specimens into a plurality of groups, and subjecting them to different subsequent treatment specimens; Step 2: Obtain the Debye ring and export the Debye ring data The room temperature samples obtained in different states were subjected to synchrotron radiation high-energy X-ray diffraction experiments, and the data of the β(110), β(200), α(0002), and α(10_1_1) diffraction rings in the sample Debye rings, where the diffraction intensity changes significantly with the azimuth angle, were extracted and plotted into a diffraction intensity-azimuth angle relationship diagram; Step 3: Analyze the preferred orientation of the main texture Analyze the preferred orientation of the main texture according to the angle and intensity information in the diffraction intensity-azimuth; Step 4: Analyze and obtain the texture change trend Combined solid solution occurs p →β transformation, most of the equiaxed α phase is dissolved in the matrix phase; β→α s transformation, the needle-shaped secondary α phase precipitates from the matrix phase, and the changing trend of the solution aging texture is compared and analyzed; Step 5: Develop heat treatment process The types and strengths of the textures in the multiple groups of cylindrical specimens are compared to find the group with the least texture, and a heat treatment process for obtaining a titanium alloy with uniform and isotropic structure is developed and improved according to the heat treatment process it has undergone.

7. The method for determining the titanium alloy texture and formulating the titanium alloy heat treatment process according to claim 6, It is characterized in that The cylindrical specimens were divided into three groups, which were subjected to solution treatment + high temperature aging treatment, solution treatment + low temperature aging treatment, and solution treatment + low temperature aging + high temperature aging treatment, and were air-cooled to room temperature after aging.

8. The method for determining the titanium alloy texture and formulating the titanium alloy heat treatment process according to claim 7, It is characterized in that The solution treatment is to perform a solution treatment on the alloy at 780-800°C for 0.5-1h and then air cool it to room temperature; The low temperature aging treatment is to age the solution treated titanium alloy at 250-350°C for 3-5h, and then air cool it to room temperature; The high temperature aging treatment is to keep the titanium alloy subjected to the low temperature aging treatment at 500-550° C. for 5-7 hours, and then air cool it to room temperature.

9. The heat treatment method according to claim 8, characterized in that: In the solution treatment, the titanium alloy is solution treated at 795° C. for 0.5 h, and then air-cooled to room temperature; In the low temperature aging, the titanium alloy is aged at 300°C for 4 hours and then air-cooled to room temperature; In the high temperature aging, the titanium alloy is kept at 520° C. for 6 hours and then air-cooled to room temperature.

10. The heat treatment method according to claim 7 or 8, characterized in that: The titanium alloy is a metastable β titanium alloy, containing 3-5 at.% Al, 5-7 at.% V, 4-6 at.% Al, 2-4 at.% Cr, 3-5 at.% Al, 0-2 at.% Zr, and the remainder is Ti and unavoidable impurities.

Citation Information

Patent Citations

  • Visual grazing incidence diffraction data processing method, system, medium and equipment

    CN116071329A

  • Method for evaluating metallographic structure based on aggregate structure and method of manufacturing steel material using evaluation method thereof

    JP2020173157A

  • Titanium alloy of low young's modulus

    US20070163681A1